FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR - Michellin, Ivana; Wijaya, Henryanto (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This study aims to determine the effect of profitability, firm size, asset structure and liquidity on the capital structure of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020. This study used a sample of 246 data. This study uses a sample selection technique with purposive sampling and uses Eviews 12 in processing the data. The results showed that profitability, firm size and asset structure had a positive and significant effect on capital structure. Meanwhile, liquidity has a negative and insignificant effect on capital structure. profitability, firm size, asset structure and liquidity simultaneously affect the capital structure.